2016
DOI: 10.1155/2016/7415438
|View full text |Cite
|
Sign up to set email alerts
|

The Identification of Microdeletion and Reciprocal Microduplication in 22q11.2 Using High-Resolution CMA Technology

Abstract: The chromosome 22q11.2 region has long been implicated in genomic diseases. Some genomic regions exhibit numerous low copy repeats with high identity in which they provide increased genomic instability and mediate deletions and duplications in many disorders. DiGeorge Syndrome is the most common deletion syndrome and reciprocal duplications could be occurring in half of the frequency of microdeletions. We described five patients with phenotypic variability that carries deletions or reciprocal duplications at 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…22q11.2 deletion is the second most common cause of congenital heart disease and developmental delays, and the most common cause of syndromic palatal anomalies [15]. The chromosome 22q11.2 region contains eight low copy repeats, which are known to lead to increased genomic instability and mediate deletions and duplications [21]. Current microarray technology has increased our ability to detect these copy number variations and aid in the diagnosis of patients with multiple congenital anomalies [22].…”
Section: Andandmentioning
confidence: 99%
“…22q11.2 deletion is the second most common cause of congenital heart disease and developmental delays, and the most common cause of syndromic palatal anomalies [15]. The chromosome 22q11.2 region contains eight low copy repeats, which are known to lead to increased genomic instability and mediate deletions and duplications [21]. Current microarray technology has increased our ability to detect these copy number variations and aid in the diagnosis of patients with multiple congenital anomalies [22].…”
Section: Andandmentioning
confidence: 99%
“…22q11.2 deletion syndrome was traditionally detected as megabase (mb) deletions including TBX1 gene in the region resulting in syndromic features of DGS and VCFS. However, an increasing number of studies using chromosome microarray (CMA) have reported a significant number of symptomatic patients harboring smaller 22q11.2 microdeletions, with some as small as 100 kilobase (kb), with or without TBX1 gene [ 1 , 3 , 4 , 7 ]. Moreover, several studies involving DGS/VCFS patients diagnosed before genetic testing was widely available have reported an increasing variation of phenotypes, including non-classic phenotypes such as genitourinary abnormalities, prematurity, and skeletal defects [ 1 , 8 11 ].…”
Section: Introductionmentioning
confidence: 99%